Pengaruh Motivasi Kerja Dan Pengembangan Sumber Daya Insani Terhadap Produktivitas Kerja (Studi Kasus Pada Karyawan Bank Syariah Indonesia Area Palembang) - Widian Anggraeni; Lemiyana; Yusiresita Pajaria (CV. ITTC INDONESIA, 2024)
This research aims to test and analyze empirically the influence of work motivation and human resource development on work productivity among employees of Bank Syariah Indonesia in the Palembang Area. The data collection technique was carried out using a questionnaire data collection method using a Likert scale. The population in this study were employees of Bank Syariah Indonesia Palembang Area. The sample was 57 respondents using a saturated sampling technique. The data obtained was analyzed using the PLS (Partial Least Square) analysis technique via SmartPLS Software and the SPSS 25 application. Where it was partially processed using the PLS analysis technique while simultaneously it was processed using the SPSS 25 application. Based on the research results, it can be concluded that: (1) Work motivation does not have a positive and significant effect on work productivity, (2) Human resource development has a positive and significant effect on work productivity, (3) Simultaneously (overall) work motivation and resource development humans have a positive and significant effect on work productivity.